Competitive Differentiation Through Sustainability: Bank Jago’s Strategic Response to Inter-Firm Competition - Hadi Cahyadi; Yohana F. Cahya Palupi Meilani; Ardi Ardi (Universitas Pelita Harapan, 2025)
This study aims to analyze the strategic responses of Bank Jago, a leading digital bank in Indonesia, to the evolving competitive landscape shaped by fintech innovation and regulatory dynamics. Employing a qualitative case study approach, this research draws on Bank Jago’s annual reports, industry analyses, and news sources, applying PESTEL, Porter’s Five Forces, SWOT, SPACE matrix, and Strategic Sustainability frameworks to comprehensively evaluate the bank’s external environment, competitive position, internal capabilities, and competitive differentiation through sustainability. The findings indicate that Bank Jago benefits from supportive government policies, rapid technological advancements, and a growing urban, tech-savvy customer base, while facing challenges such as stringent regulatory requirements, rising competition from regional fintech firms, and economic volatility. Strategic partnerships, particularly with fintech platforms like Gojek, and innovative digital banking services such as the ‘Pockets’ feature, have strengthened Bank Jago’s market position. The SPACE matrix analysis suggests an aggressive strategic posture, emphasizing growth and innovation to capitalize on market opportunities. The study concludes that Bank Jago’s adaptive strategies, focused on digital transformation, customer-centric innovation, regulatory compliance, and environmental sustainability, will be pivotal for its sustained competitive advantage and expansion in Indonesia’s digital banking sector.